2007
DOI: 10.1016/j.cbpa.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The nervous system control of lateral ciliary activity of the gill of the bivalve mollusc, Crassostrea virginica

Abstract: Lateral cilia of the gill of Mytilus edulis are controlled by a reciprocal serotonergic-dopaminergic innervation from their ganglia. Other bivalves have been studied to lesser degrees and lateral cilia of most respond to serotonin and dopamine when applied directly to the gill indicating a possible neuro or endocrine mechanism. Lateral cilia in Crassostrea virginica are affected by serotonin and dopamine, but little work has been done regarding ganglionic control of their cilia. We examined the role of the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 43 publications
5
45
0
Order By: Relevance
“…Previous experimental studies have reported a noticeable dose-dependent increase of TH in the gills of M. galloprovincialis exposed to 0.1, 1, 10 μg Cr(VI) L − 1 animal −1 for 96 h (Ciacci et al, 2012). The increase in TH may result in the enhancement of dopaminergic neurotransmission that has an inhibitory effect on lateral ciliary activity of mussel gills (Carroll and Catapane, 2007). Zhu et al (2005) demonstrated that tyrosine and tyramine may augment endogenous ganglionic morphine and dopamine levels in Mytilus edulis under in vitro and in vivo experiments, with the involvement of CYP2D6 and TH in the process, resulting in a cilioinhibitory effect.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous experimental studies have reported a noticeable dose-dependent increase of TH in the gills of M. galloprovincialis exposed to 0.1, 1, 10 μg Cr(VI) L − 1 animal −1 for 96 h (Ciacci et al, 2012). The increase in TH may result in the enhancement of dopaminergic neurotransmission that has an inhibitory effect on lateral ciliary activity of mussel gills (Carroll and Catapane, 2007). Zhu et al (2005) demonstrated that tyrosine and tyramine may augment endogenous ganglionic morphine and dopamine levels in Mytilus edulis under in vitro and in vivo experiments, with the involvement of CYP2D6 and TH in the process, resulting in a cilioinhibitory effect.…”
Section: Discussionmentioning
confidence: 94%
“…The rise of 5-HT 3 R could be related to an adaptive response mediated by paracrine signaling activities in order to recover a regular physiological activity in gills. Indeed, it has been reported that gill epithelial cells containing the lateral cilia present 5-HT receptors to increasing the ciliary beating rate, if activated (Carroll and Catapane, 2007). Fabbri and Capuzzo (2006), after exposing mussel M. galloprovincialis to Cr(VI) and Cu(II), found increased 5-HTstimulated adenylate cyclase activity in vivo, and suggested the possibility that metal accumulation in mussel gills might induce the overexpression of 5-HT receptors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dopamine has been shown to be a component inhibitor of lateral cilia activity in all tested bivalve species (Jørgensen, 1976;Malanga, 1974;Carroll and Catapane, 2007); however, it has no effect on latero-frontal cilia (Jørgensen, 1976) and may stimulate the activity of frontal cilia (Malanga, 1975). Dopamine is also known to stimulate glycolysis (Malanga, 1974) and relax catch muscles (Twarog and Cole, 1972).…”
Section: Experimental Incubation Protocolsmentioning
confidence: 99%
“…Serotonin is known to increase activity of different types of cilia in molluscs (Audesirk et al 1979;Beiras and Widdows 1995;Uhler et al 2000 Carroll andCatapane 2007). For example Beiras and Widdows (1995) showed increased swimming activity of M. edulis larvae after exposure to serotonin, which enhanced movement of velar cilia.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%